COMBINING GENERATIONAL GENETIC AND LP(A) CASCADE TESTING TO PREDICT LP(A) AND ASSOCIATED CARDIOVASCULAR DISEASE (CVD) RISK IN YOUNG ADULTS - Jamal A Anthony; Tatiana Echeverry; Robert D Fishberg (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD Risk Assessment Background: Like Familial Hypercholesterolemia (FH), Lp(a) ≥300nmol/L is associated with 3-4-fold increased cardiovascular risk but is more common. Cascade screening of first-degree relatives for FH has been widely accepted but not commonly used for Lp(a). In Caucasian populations, variants of Single Nucleotide Polymorphisms (SNPs) rs10455872 and rs3798220 have the greatest impact on Lp(a) levels. Progression of coronary artery disease (CAD) and aortic stenosis has been particularly associated with the rs10455872.We present a case of how cascade screening using 23andme, direct-to-consumer genetics, identified rs10455872 genotypes, A/A (low risk), A/G (moderate risk) and G/G (high risk) in a family, allowing prediction of Lp(a)-associated risk in their youngest generation. Methods: A 59-year-old male was found to have a calcium score of 1587. Catheterization revealed high-grade stenoses in the LAD and diagonal artery which were stented. Lp(a) was 163 nmol/L. He arranged 23andme and Lp(a) testing of 22 family members over 3 generations. The relationship between genotypes and Lp(a) was analyzed in generations 1 & 2 and used to predict Lp(a) risk category (See figure 1) of generation 3. Results: The rs3798220 genotype was normal, but abnormal rs10455872 genotypes were prominent. Our patient was A/G. His wife was A/G (Lp(a): 238 nmol/L). His asymptomatic mother-in-law was G/G (Lp(a) 448 nmol/L). One of his children had A/A genotype, 2 had A/G and one had G/G. A positive correlation was found between genotype and Lp(a). This allowed accurate prediction of Lp(a) risk category for each child based on their genetics. We predicted that his daughter who was G/G, would have an Lp(a) ≥300 nmol/L. Her Lp(a) was 312 nmol/L placing her in the very high-risk category (Figure 1). Conclusion: Through combined genetic and Lp(a) cascade testing we identified individuals with increased CVD risk. 23andme was effective in identifying the most common LPA genotypes. If a positive correlation between genotype and Lp(a) is found in older generations of families, Lp(a)-associated CVD risk in younger generations can be estimated. Caution should be taken with this approach in non-Caucasian populations since other SNPs may be responsible. Studies including more diverse populations should be done to validate this approach to identify high-risk individuals who may benefit from more aggressive primary prevention.